Dinamika populasi ikan belanak, Chelon subviridis (Valenciennes, 1836) di muara Sungai Opak - Yogyakarta - Djumanto Djumanto; Mike Gustiana; Eko Setyobudi (Jurnal Iktiologi Indonesia, 2015)
reenback mullet (Chelon subviridis) is the main species of fish catches in the estuary of Opak River Yogyakarta. The study of the population dynamics becomes important as a basis for fisheries management tools, so that mullet fish stocks can be utilized in a sustainable manner. The purpose of this study was to assess the population parameter of mullet in the area. Fish sampling was done biweekly from the middle of July 2012 to May 2013. Fish catching was done using gillnets wi-th various mesh size. All samples of mullet were collected and sexed, total length was measured using a metal ruler and weighted using digital scales. Length frequency data were analyzed using the software of FiSAT II to estimate the parameters of growth, mortality and recruitment. The results showed that, for the male mullet, VBGF growth parameters, namely L®, K, and to was 29.93 cm, 0.23 and -0.22, respectively. The total mortality, natural mortality and fishing mortality was 1.21, 0.69, and 0.52 per year, respectively, and the exploitation rate was 0.42. In the female, the VBGF growth parameters L ®, K, and to was 37.28 cm, 0.34 and -0.35, respectively. The total mortality, natural mortality and fishing mortality was 1.56, 0.84 and 0.72 per year, respectively, while the exploitation rate was 0.46. Recruitment patterns occur each year with peak spawning was estimated at the beginning and ending of the dry season. Abstrak Ikan belanak (Chelon subviridis) merupakan salah satu jenis ikan tangkapan utama di muara Sungai Opak, Yogyakarta. Kajian dinamika populasi menjadi penting sebagai dasar pengelolaan perikanan agar stok ikan belanak dapat dimanfaatkan secara berkelanjutan. Penelitian ini bertujuan untuk mengkaji parameter populasi ikan belanak di muara sungai tersebut. Pengambilan contoh ikan dilakukan setiap pertengahan bulan dari Juli 2012 hingga Mei 2013. Penangkapan ikan menggunakan jaring insang berbagai bukaan mata jaring. Semua contoh ikan belanak yang tertangkap diidentifikasi jenis kelaminnya melalui pembedahan, diukur panjang total menggunakan mistar logam dan berat individu menggu-nakan timbangan digital. Data frekuensi panjang dianalisis menggunakan perangkat lunak FiSAT II untuk menduga parameter pertumbuhan, mortalitas dan rekrutmen. Hasil penelitian pada belanak jantan menunjukkan parameter pertum-buhan VBGF L®, K, dan to adalah 29,93 cm, 0,23 dan -0,22; mortalitas total 1,21 per tahun, mortalitas alami 0,69 dan mortalitas penangkapan 0,52 per tahun serta tingkat eksploitasi sebesar 0,42. Pada belanak betina diperoleh parameter pertumbuhan VBGF L®, K, dan to adalah 37,28 cm, 0,34 dan -0,35; mortalitas total 1,56 per tahun, mortalitas alami 0,84 dan mortalitas penangkapan 0,72 per tahun serta tingkat eksploitasi sebesar 0,46. Pola rekrutmen terjadi setiap tahun dengan puncak pemijahan diperkirakan pada awal dan akhir musim kemarau.